COMPILATION OF CATALOG OF STELLAR EQUATORIAL COORDINATES AND B-MAGNITUDES USING UKRVO PLATE DATABASE - Andruk, V. N.; Golovnya, V. V.; Ivanov, G. F.; Izhakevich, E. M.; Pakuliak, I. K.; Protsyuk, Yu. I.; Shatokhina, S. V.; Yatsenko, A. I.; Muminov, M. M. (Одеські астрономічні публікації, 2014)
To ensure the rational use of informational resources generated by UkrVO in MAO NASU, a catalog of equatorial coordinates (α, δ) and B-magnitudes of stars was created by using plates obtained during observational campaign named FON (ukr., Photographic Sky Survey). 102 plates with field of view of 8° were processed. Digitization of plates with sizes of (30x30) cm or (13000x13000) px was performed by using resolution of 1200 dpi. The catalog contains astrometric data for 1, 263, 932 stars and galaxies with B ≤ 16.5m at epoch 1984.76. The coordinates and B magnitudes were respectively obtained in the system of TYCHO-2 catalogue and photoelectric standards. The internal accuracy of the catalog: for all objects is ±0.26" for coordinates and ± 0.17m for magnitudes, and for stars in the range B = 8m -13m is ± 0.13" and ± 0.11m. Convergence of coordinate with reference TYCHO-2 system is ±0.06" (for 93 925 stars), the convergence with the photoelectric stellar B-magnitudes is ±0.16m (for 4458 stars). Errors relative to the UCAC-4 catalog are ±0.34". We identified 1099005 stars and galaxies.